Handling, Conditioning of Low Level Radioactive Wastes (LLRW), Spent Radiation Sources (SRS), their transport to Temporary Storage Facility in Kosovo and Albania - Cena, Besire; Qafmolla, Luan; Hasi, Nazmi (International Journal of Computational and Experimental Science and Engineering, 2024)
The paper is intended to provide reference material, guidance and know-how on handling, conditioning and storage of spent sealed radioactive sources (SRS) to both users of sealed sources and operators of waste management facilities. Due to the limited availability of disposal practices for spent SRS, disposal is covered in a broad context only. Aspects of handling, conditioning, and storage of spent sealed radioactive sources resulting from the use of radioisotopes and radiation sources in research, medicine, industry, and agriculture are described. The paper presents the current situation in Kosovo and Albania regarding the management of low-level radioactive waste, temporary interim storage and their system until final disposal, taking into account the IAEA documents on this topic. The methods applied for the conditioning of LLRW and SRS are simple. The important point after the inventory of radioactive waste was their location and the ID (identifying number) of the radioactive sources, based on the type of radioisotopes and their activity. The paper contains in some detail technical procedures for the conditioning of spent SRS, describes the means required to assure the quality of the resulting package and discusses the measures to prepare waste packages with a certain flexibility to accommodate possible future disposal requirements.